Standard and pegylated interferon therapy of HDV infection: A systematic review and meta- analysis - Alavian, Seyed-Moayed (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Hepatitis D virus (HDV) infection is characterized by rapidly progressive liver disease with adverse prognosis in most patients. Although interferon is the only approved anti-HDV therapy, evidence regarding the efficacy and safety of its various regimens is either old or scattered. MATERIALS AND METHODS: We searched systematically Medline, EMBASE, Scopus, the Cochrane Central Register of Controlled Trials, and ISI. The studies that evaluated treatment of chronic HDV infection with standard or pegylated interferon for at least 48 weeks were identified. Our inclusion criteria were positive anti-HDV antibody for 6 months and positive HDV-PCR at the start of study. We performed a meta-analysis for proportions using the arcsine transformation in random effects model. Sustained virological response (SVR) rate (negative Polymerase chain reaction (PCR) 6 months after cessation of therapy) was the end point of interest. RESULTS: Data were abstracted from 14 studies containing 227 chronic HDV-infected patients who received standard or pegylated interferon alpha-2a or -2b. Twenty-one and 30 patients of 71 and 156 who received standard or peginterferon, respectively, beyond 48 weeks achieved SVR. Pooled SVR rates were 29% [95% confidence interval (CI) 19; 41] and 19% (95% CI 10; 29), respectively. The rates of treatment withdrawal were similar. CONCLUSION: Our systematic review indicates that the literature lacks sufficient evidence to establish precise recommendations for treatment of HDV infection. Meta-analysis of these studies shows that standard dose of peginterferon is more effective than high dose of standard interferon as anti-HDV therapy.